Repeatability of a bending stiffness test for snowboarding wrist protectors - Leslie, G.; Winwood, K.; Wang, W.; Hamilton, N.; Allen, T. (Sports Engineering, 2023)
Snowboarding wrist protectors are typically designed to limit impact forces and prevent wrist hyperextension. The standard for snowboarding wrist protectors (ISO 20320:2020) includes a test for measuring their bending stiffness, when fitted to a wrist surrogate. This test serves as a simple means of assessing the ability of wrist protectors to prevent wrist hyperextension. Wrist protector bending stiffness measurements have been shown to be influenced by surrogate design, protector strapping condition, and surrogate surface compliance. Currently, there is a lack of knowledge on the repeatability of bending stiffness measurements, as previous studies have conducted tests during one session. This study investigated the repeatability of a bending stiffness test, by testing two snowboarding wrist protectors (short and long) on two wrist surrogates (compliant and stiff), under three protector strapping conditions (loose, moderate, tight), across three repeated test sessions. Test session had a significant effect (p < 0.05) on torque values, with a large effect size (?2p > 0.14), indicating the test had limited repeatability between test sessions. Despite this limited repeatability, torque values increased with both wrist angle and strap tightness, as reported before, indicating consistent trends in results. The outer surface compliance of the surrogate did not significantly affect the protector`s sensitivity to test session nor strapping condition.